Sexuality and the Gothic Magic Lantern - Jones, D. author. aut Link
X, 254 p.
Keywords: This fascinating study explores the multifarious erotic themes associated with the magic lantern shows, which proved the dominant visual medium of the West for 350 years, and analyses how the shows influenced the portrayals of sexuality in major works of Gothic fiction.